A integralidade na prática clínica e institucional e na relação ensino-serviço: um estudo de caso sobre a formação do psicólogo em hospital público - SOUZA, Ana Vicentina Santiago de (Universidade Federal do Pará, 2014)
This work consists of studying the clinical and institutional practice in the psychologist’s formation under the perspective of the totality in health in the João de Barros Barreto Academical Hospital - HUJBB. The choice of the study field was due to the knowledge of the hospital while work area, as well as for the fact of this to be one of the three only places in Unique Wealth System SUS that serve as practice for the Course of Psychology of UFPA, where it is propitiated the students to have contact with the clinical and institutional practice, applying theoretical-methodological backgrounds of Psychoanalysis, institutional analysis, processes group and of communication and knowledge of Public Health. Being used of the qualitative approach, the procedures of collection of data were the semi-structured interview, the questionnaires and the participant observation. Among the important aspects in the study was observed: the constant fragmentation of the several involved professionals’ work and the psychologist’s search for a space more consolidated and articulate of performance in the team of health; the lack of previous knowledge of collective health on the part of the students motivating a concentrated effort of the supervisors and field advisors in the relationship teaching-service; the failed of the physical facilities and of the equipments of the hospital generating difficulties, but, simultaneously, stimulating an expressed subjectivity in the collaboration between employees and students; the effort of the Service of Psychology in drill the work centered in the medical act and in the sick body for an attention marked by the relationship with the patient as subject and for the different manners of psychopathologic subjectivization that constitute the theoretical-methodological problem placed for your psychotherapic effectiveness; and, finally, its insert in the teams multiprofessionals. The plot formed by the group of those protagonisms it configures the psychologist’s challenge, with the other professionals, to understand and to carry out the wholeness of the attention, in permanent exercise of construction in the hospital. Two theoretical stand out in the argument that problematizes the integral attention in the hospital - Canguilhem, for the discussion of the concept of health while possibility to live in conformity with the middle and Winnicott, in the possible clinical perspective in that adapts.